Variasi Sebutan untuk Kucing dan Pemaknaannya dalam Akun Mention Confess (Menfess) @Kochengfs - Puspitaningsih, Lestari; Monalisa, Monalisa (MIMESIS, 2024)
Variations in the appellation of cat are created because cat is marked as something important for humans. One influential factor in the emergence of variations in the appellation is the existence of interaction spaces among cat lovers. One of them is menfess account @kochengfs. This research examines the various appellation for cat and their meanings in the menfess account @kochengfs. The purpose of this research is to describe the variation of appellations for cat and their meanings in the menfess account @kochengfs. This research is included in the qualitative descriptive research. This research uses a semiotic approach with the trichotomous relation theory from Peirce. The data source of this research comes from the mention confess (menfess) account @kochengfs with a corpus of research data in the form of 1,758 tweets taken from 17–24 February 2023. Based on the analysis, there are 214 tweets containing 37 appellations for cat. The appellations are dominated by icon signifying with a total of 24 appellations, then symbols with 12 appellations, and index only 1 appellation. Appellations with icon signifying are based on (a) body shape; (b) body hair; (c) voice imitation; (d) fur color; (e) teeth shape; and (f) physical characteristic.